Analisis Dampak Kebijakan Pariwisata Berkelanjutan Terhadap Kunjungan Wisatawan Dan Ekonomi Masyarakat Di Kadaka Hills Tanjungsari - Setiawati, Sari; Ramdani, Dadan (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of implementing sustainable tourism policies on tourist visits and the local economy at Kadaka Hills Tanjungsari. The research method used was a qualitative approach, with data sources from tourism managers, MSMEs, tourists, and the surrounding community. The results indicate that the implementation of sustainable tourism policies has had a positive and significant impact on increasing tourist visits to Kadaka Hills. Implemented policies, such as the development of environmentally friendly infrastructure, nature conservation programs, and local community empowerment, have proven effective in attracting tourists. Furthermore, tourists are satisfied with their travel experiences at Kadaka Hills, which prioritize sustainability. The implication of this study is the need for commitment from the local government and other stakeholders to continue developing and promoting Kadaka Hills as a sustainable tourism destination that can improve the welfare of local communities. This research is expected to serve as a reference for the development of sustainable tourism in other destinations in Indonesia, which impact the local economy.